Extraction and identification of di(2-ethylhexyl) phthalate from safed musli (chlorophytum borivilianum L.) - Chua, Bee Lin (2015)
Chlorophytum borivilianum (safed musli) is a medicinally important plant. Its roots are being employed in folk medicine. Presently, the crude extract of C. borivilianum has been consumed for the treatment such as anti-diabetic, anti-aging, anti-oxidant, anti-ulcer and anti-inflammatory. Studies have been carried out to further confirm these remarkable bioactivities of C. borivilianum. So far, the isolated chemical constituents are mainly saponins. A fructo-oligosaccharide, three fatty acids, one sterol stigmasterol, hecogenin also have been reported to be isolated from the roots of C. borivilianum. In this research,di(2-ethylhexyl) phthalate (DEHP) was extracted from the aqueous extract of the roots of C. borivilianum. The yield of DEHP was found to be 33.70 mg, which was equivalent to 0.013% with reference to the total weight of root powder (250 g). The structure of DEHP was elucidated based on the spectral data of 1H-NMR, 13C-NMR, distortionless enhancement by polarization transfer (DEPT), correlation spectroscopy (COSY),heteronuclear multiple bond correlation (HMBC) and heteronuclear multiple quantum correlation (HMQC) and also based on the comparison with the previous literature data. This is the first report so far of occurrence and detail spectroscopic description of DEHP from C. borivilianum. Single experimental design and response surface methodology (RSM) was implemented to optimize the extraction conditions for obtaining the maximum yield of DEHP from the roots of C. borivilianum. DEHP was optimized because it could be a starting point to pave a way to isolate and quantify other pure compounds (minor or rare) from this herbaceous plant in order to use it as a tool for quality control and also for the future development of other therapeutic applications. Furthermore, DEHP was reported to possess some remarkable biological activities such as anti-leukemic, anti-microbial, anti-fungal, anti-tumour and antiviral activity against H1N1 disease. In this study, ultrasound-assisted extraction was applied for the effective extraction of DEHP and DEHP was quantified by high performance liquid chromatography (HPLC) analysis. Herein, three independent variables (extraction time, solid to solvent ratio and extraction temperature) with a five level design were evaluated using the central composite design (CCD), with the yield of DEHP as the response variable. Second-order polynomial model was found to be satisfactory in describing the experimental data for the total DEHP content. The analysis of variance (ANOVA) indicated that the main effect of solid to solvent ratio and the extraction temperature as well as the quadratic effects of all independent variables had significant effect ("Prob>F"<0.05) on the extraction yield of DEHP. The optimal extraction conditions were established as follow: extraction time of 92 min, solvent to solvent ratio of 1:38 (g/mL) and extraction temperature of 51°C. Using these adjusted optimal conditions, the predicted yield of DEHP by model was 0.44 ppm whereas the actual yield of DEHP was 0.43±0.01 ppm which was in close conformity with the predicted values as the relative error was just 2.72%. The extraction kinetic was studied using equilibrium extraction model (EEM) and diffusion extraction model (DEM). The kinetics results revealed EEM model was more suitable in describing the extraction process and the ethanol extraction of the roots of C. borivilianum achieved equilibrium within 70 minutes. Lastly, DEHP extracted from the roots C. borivilianum was tested for its anti-inflammatory activity. However, DEHP had shown a low inhibition effect on the anti-inflammatory activity in HYA assay with a percentage of inhibition of 4.02±1.17%. This study implied that DEHP was not active to inhibit the hyaluronidase enzyme and this indicated that the other compounds in the roots of C. borivilianum might contribute to the antiinflammatory activity as the previous researchers had obtained significant antiinflammatory activity from this plant.